Negative effects of digital media on the psychophysical development of preschool-aged children - Mićević Karanović, Jelena Ž.; Mesaroš Živkov, Angela J.; Pavlov, Srbislava V.; Brkljač, Tanja S. (Sinteze - časopis za pedagoške nauke , književnost i kulturu, 2021)
The main goal of this research was to determine how familiar preschool-aged children are with certain digital media (internet, social media, mobile phones and computers), how much they use them, what they think about the negative effects of their influences and how much protection from these negative effects their parents and preschool teachers offer. The main method was non-experimental – a survey research on a sample, and the research sample consisted of 110 preschool-aged children. The sample was purposeful and convenient, which suited the exploratory nature of this research. The instrument used is a modified and shortened version of the questionnaire constructed for a broader research project. The results obtained show that the majority of preschool-aged children know what digital media are, that they use them and that they have not had negative experiences when facing them, as well as that they sometimes talk to their parents and kindergarten teachers about the dangers and risks of using digital media. Parents do control the using of digital media, but they more often decide to ban them than to talk to their children about their negative effects, even though it is indicative that prevention, in terms of educating the children, i.e. talking to them and properly informing them on the negative influences of digital media is a better option than strict control and banning their use.
Keywords: digital media; CHILDREN; parents; Preschool-Age Children; media